Optimisation of LS54/Dx Aqueous Two Phase System Conditions for Cutinase Recovery - Jamaliah Md. Jahim; Abdul Wahab Mohammad; Fariza Akmal Abdul Mutalib; Farah Diba Abu Bakar; Osman Hassan (ASEAN Journal of Chemical Engineering, 2012)
Aqueous two phase system comprising Dehypon® LS 54 and K4484 Dextrin® was selected for recovery of cutinase enzyme. Parameters such as pH, system composition and type of salt as an additive, influenced the protein partitioning behaviour and optimisation of these parameters become necessary to be done in the design of primary recovery process of ATPS. The cutinase partitioning experiments were carried out with 30% of cutinase solution added to LS 54/Dx system. Results showed that cutinase enzyme preferred to partition into LS 54 rich-phase at pH 8.0 and the affinity of cutinase into top phase was observed higher with the increment of system compositions, which represented by tie line length (TLL). Furthermore, the addition of 50mM salts such as K2SO4 and KCl into LS 54/Dx system has led to raise partition coefficient of cutinase, kcut to 2.2 and 1.95 fold, respectively. The dependence of kcut on various additives such as (NH4)2SO4, Na2SO4 and K2SO4 at the same concentration, suggested that the addition of selected ions could enhance positive electrostatic potential which could attract more cutinase to partition into LS54 rich phase. As conclusion, the best conditions obtained for cutinase partitioning were pH8.0, TLL = 23% and Na2SO4 = 50mM, from which the maximum kcut of 2.83 with improved recovery of cutinase in top phase up to 79% can be achieved.